The Effect of Skills and Motivation on Employee Performance with Job Satisfaction as Intervening Variables - Devi Dzumirotin Rahmatika; Achmad Mohyi; Siti Nurhasanah (Universitas Muhammadiyah Malang, 2022)
This research aims to determine and analyze the effect of skills and motivation on employee performance with job satisfaction as an intervening variable at Industry Center Keripik Tempe Sanan Malang. This type of research used is explanatory research using a quantitative approach. This data collection technique used questionnaires with sampling technique used saturation sampling with 100 respondents. This data analysis technique used SEM-PLS. Based on the result of the analysis, employee performance, skills, and motivation are in the high category, while job satisfaction is in the satisfied category. Skills have a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance. Skills have a positive and significant effect on job satisfaction. Motivation has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Skills have an effect positive and significant on employee performance through job satisfaction as an intervening variable. Motivation has a positive and significant effect on employee performance through job satisfaction as an intervening variable.